The Effect Counseling on the Knowledge Women of Fertile Age (Wus) About Mow Contraception (Women's Surgery Method) - Betristasia Puspitasari (Sean Institute, 2026)
MOW contraception is a long-term contraceptive method that has a relatively low failure rate and is free from side effects. However, interest in MOW contraception is still low, compared to other long-term contraceptives. The low interest of mothers in choosing female surgical contraception (MOW) can be influenced by several factors. These factors include internal factors or factors within the individual such as age, number of children, health factors, education, knowledge, and attitudes. Meanwhile, external factors include facilities and infrastructure, costs and side effects of the contraceptive, husband's support, support from health workers, and information about the MOW contraceptive method. The purpose of this study was to determine the effect of counseling on the knowledge of women of fertile age (WUS) about female surgical contraception (MOW). The research design used is a pre-experimental research design, namely One Group Pre-Test and Post-Test. The population in this study were all WUS in RT 02 RW 02 Sidomulyo Village, Semen District, Kediri Regency, totaling 33 people with a total sampling technique. The independent variable in this study is counseling about the MOW contraceptive method and the dependent variable is the knowledge of PUS women about the MOW contraceptive method. Counseling was given to groups of women of childbearing age who already have children. The counseling media used were MOW contraceptive counseling materials, LCDs, and laptops. Data collection used a questionnaire totaling 15 questions. The questionnaire for the pre-test and post-test was the same and had been tested for validity and reliability. Data processing used editing, coding, scoring, tabulating and presented. The analysis used was the Wilcoxon Match Pair test. The results of the study showed that of the 33 respondents studied, before the counseling, most had sufficient knowledge, namely 25 respondents (75.76%), after the counseling, most had good knowledge, namely 28 respondents (84.84%). From the results of the data analysis test, the Z result was -5.533 with a significance level (σ) of 0.000 (σ ≤ 0.05). Because σ ≤ 0.05, H1 is accepted, which means there is an effect of counseling on the knowledge of women of fertile age (WUS) about female surgical methods (MOW) of contraception. Based on the research results above, counseling has an impact on the knowledge of women of childbearing age. Counseling has a positive impact on increasing knowledge of women of fertile age about MOW contraception. Therefore, counseling from health workers is crucial and essential to increase knowledge and support women of fertile age (WUS) in choosing female surgical methods (MOW) of contraception.